1993
DOI: 10.1007/bf00131561
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of pyrite by Acidianus brierleyi: Importance of close contact between the pyrite and the microorganisms

Abstract: Experiments were done in order to study the thermophilic archaebacterium Acidianus brierkyi during oxidation of pyrite (FeS$. The microorganisms were grown both separated from the pyrite by a membrane and in close contact with the pyrite. From the results it can be concluded that direct contact is needed for good growth of the strain studied. The obtained results indicate that the direct contact mechanism may be applied to oxidation of sulfidic minerals by A. brierleyi. IntroductionThere is a large degree of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…, which then in turn oxidizes the Fe 2? on the pyrite surface in a strictly abiotic and chemical process (Larsson et al 1993;Fowler et al 1999;Rohwerder et al 2003). The produced Fe 3?…”
Section: Introductionmentioning
confidence: 96%
“…, which then in turn oxidizes the Fe 2? on the pyrite surface in a strictly abiotic and chemical process (Larsson et al 1993;Fowler et al 1999;Rohwerder et al 2003). The produced Fe 3?…”
Section: Introductionmentioning
confidence: 96%
“…Within coal mining regions, oxidation of the mineral, which is facilitated by the presence of microbes, leads to the environmental phenomenon known as acid mine drainage (AMD), that impacts ecosystems primarily through a sulfuric acid laden runoff (Larsson et al, 1993;Nordstrom and Southam, 1997;Edwards et al, 1998;Marchand and Dinkelman, 2006). With an eye toward understanding the chemistry associated with AMD, there has been a significant effort focused on studying the mechanistic details of pyrite oxidation under abiotic and biotic conditions (Shrihari et al, 1991;Solari et al, 1992;Ohmura et al, 1993;Edwards et al, 1999;Elsetinow et al, 2000;Borda et al, 2003;Elsetinow et al, 2003;Hao et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of attachment on oxidative dissolution rates is unresolved. In one study using an iron-oxidizing archaea, Larsson et al (1993) showed that close contact between microorganisms and pyrite was necessary for optimum growth and oxidation rates. However, attachment to the sulfide surface did not appear to be necessary.…”
Section: Introductionmentioning
confidence: 99%